Peran Komite Sekolah Dalam Peningkatkan Mutu Pendidikan Di SD Negeri 3 Terkesi Kecamatan Klambu Kabupaten Grobogan - Budi Prihanto, Agus, Dr. Sabar Narimo,MM,M.Pd, Dr. A.Muhibin, M.Si (2017)
The purpose of this research is 1) to describe the role of the school committee in encouraging the participation of the community in improving the quality of education in SD Negeri 3 Terkesi. 2) to describe the efforts made by the school committee to improve the quality of education in SD Negeri 3 Terkesi. 3) to describe the constraints of the school committee in support of quality improvement education . The techniques of data collection observation, interviews and documentation. Data analysis techniques of data collection, data reduction, data presentation, and conclusion. Test validity using triangulation The results of this study were 1) the real of the role of the committee SDN 3 Terkesi is actively providing understanding to the community around SDN 3 Terkesi the importance of education, encourage, mobilize public participation, around the contribution in the form of money, materials, and contribute ideas and energy to improve the quality of education especially in SDN 3 Terkesi and the surrounding environment. The school committee SD Negeri 3 Terkesi within its staff have provided a lot of contribution in improving the quality of education, consist of such as educational facilities which are providing assistance in making the school fence, manufacture MCK, program pavingisasi the yard of the school. 2) The cooperation undertaken by the school committee with SD Negeri 3 Terkesi is to enhance its role as a partner school, active work with the school to provide direction, support, control, mediator in the implementation of learning in school, so the school can improve the quality of education. 3) Constraints faced by the school committee in an effort to increase the quality of education SD Negeri 3 Terkesi namely the lack of public awareness about SD Negeri 3 Terkesi the importance of formal education, people still think that education for akhirat much more important for the children, of the other education. The perceived impact associated with mindsite school that has been believed by the public,so that the publicis less than the maximum community to be concerned with the needs of schools so that schools are no events, the program is still not fully supported by the community.